2001
DOI: 10.1002/1099-1166(200102)16:2<147::aid-gps286>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for the use of psychotropics among nursing home residents

Abstract: Purpose To characterise the prescription pattern of psychotropics in Danish nursing homes and to identify diagnostic, behavioural, cognitive and performance characteristics associated with prevalent psychotropic drug use. Methods Prescribed daily medication was recorded from nurses' files. Based on the Anatomical Therapeutical Chemical (ATC) classification index, psychotropics were categorised into neuroleptics, benzodiazepines and antidepressants. Two hundred and eight‐eight residents were diagnosed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
4

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 25 publications
5
42
4
Order By: Relevance
“…The prevalence of antipsychotic medication in this study is in line with, or somewhat lower than, that reported previously (Craig et al, 2003;Pitkala et al, 2004;Sørensen et al, 2001). Different population characteristics and methodology make closer comparisons impossible.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The prevalence of antipsychotic medication in this study is in line with, or somewhat lower than, that reported previously (Craig et al, 2003;Pitkala et al, 2004;Sørensen et al, 2001). Different population characteristics and methodology make closer comparisons impossible.…”
Section: Discussionsupporting
confidence: 84%
“…Psychotic features, agitation, offensive behavior, nocturnal disturbances, better mobility, lower age and higher body mass index have all been found to correlate with an increased risk of being treated with antipsychotics in various studies. Cognitive function and activities of daily living (ADL) dependency correlated negatively in some and positively in others (Craig et al, 2003;Lindesay et al, 2003;Robertson et al, 2000;Sørensen et al, 2001). The complex process that leads to an old person with dementia being given antipsychotic treatment, however, remains far from being fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have reported a wide range of prevalence of psychotropic prescription (10-60%) and have mainly focused on the classes of psychotropics and prevalence of psychiatric morbidity among residents. 5 Moreover, although the presence of medical illness seems to negatively affect the identifi cation of psychiatric morbidity by general practitioners, 6 there is to our knowledge no systematic study examining how the prescription of non-psychotropic drugs may infl uence the non-psychiatrist physician's decision-making process for prescribing psychotropics for the elderly in developing countries.…”
Section: Introductioncontrasting
confidence: 92%
“…This is in agreement with studies 3,5 examining the prevalence of the use of psychotropics among nursing home residents. These studies have reported rates ranging from 27% to 60%, which are higher than the rates of 9.3 to 30.6% found in community studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation